(untitled) (The Pakistan Development Review, 1999)
The private costs of electricity supply failures are substantial and inimical to industrial productivity. Using results from a small sample survey of manufacturing firms in Karachi, the study documented the causes, extent and incidence of the failures, identified and classified the firms’ private responses, and estimated the capital share of internally produced power and the associated costs. The results are reported here to engender discussion for developing a policy model of infrastructure provision suited to a developing country like Pakistan. The most encouraging options are those that allow for cooperative provision amongst firms with concurrent reforms in the regulatory and institutional environments. An optimal policy will allow inter-firm trading of electricity making the power market competitive. Those firms that already have extensive private generating capacity due to weak public supply will realise scale economies by selling electric power to lower the costs of private provision. Competition in electricity supply implies that industrial users will find attractive substitutes in the private sector. This will lead to a reduction in the demand on public service, already limited in quantity and quality in key urban-industrial locations like Karachi.